1994
DOI: 10.1002/jlb.56.5.583
|View full text |Cite
|
Sign up to set email alerts
|

Induction of superoxide anion production from monocytes and neutrophils by activated platelets through the P-selectin–sialyl Lewis X interaction

Abstract: Activated platelets expressing P-selectin on their surface are known to adhere to monocytes and neutrophils. We examined the possibility that the leukocytes were activated by their adhesion to activated platelets and demonstrated that P-selectin-dependent platelet adhesion to neutrophils and monocytes induced production of extracellular superoxide anion (O2-) by these leukocytes. Leukocyte membrane glycoproteins containing Ser/Thr-linked carbohydrate chains were responsible for the signal reception leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 26 publications
1
39
1
1
Order By: Relevance
“…Consequently, the CL-response effect of anti-PSGL-1 was especially potent under stirring conditions. Furthermore, Tsuji et al demonstrated that thrombin-activated platelets enhanced the extracellular release of superoxide anion from neutrophils via P-selectin interaction with sialyl Lewis X [47]. They also noticed, in accordance with Wong et al and the present study, that soluble recombinant P-selectin rather inhibited than potentiated the effects on the neutrophil respiratory burst [47,48].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, the CL-response effect of anti-PSGL-1 was especially potent under stirring conditions. Furthermore, Tsuji et al demonstrated that thrombin-activated platelets enhanced the extracellular release of superoxide anion from neutrophils via P-selectin interaction with sialyl Lewis X [47]. They also noticed, in accordance with Wong et al and the present study, that soluble recombinant P-selectin rather inhibited than potentiated the effects on the neutrophil respiratory burst [47,48].…”
supporting
confidence: 91%
“…Furthermore, Tsuji et al demonstrated that thrombin-activated platelets enhanced the extracellular release of superoxide anion from neutrophils via P-selectin interaction with sialyl Lewis X [47]. They also noticed, in accordance with Wong et al and the present study, that soluble recombinant P-selectin rather inhibited than potentiated the effects on the neutrophil respiratory burst [47,48]. This is probably due to that isolated platelet P-selectin is dimeric, both in -granules of resting cells and on activated platelet surfaces [49].…”
mentioning
confidence: 99%
“…It is known that oxidative stress favours both apoptosis and anergy of T lymphocytes (Buttke and Sandstrom, 1994) and that G-CSF enhances superoxide production by mature neutrophils (Tsuji et al, 1994). The effects of the superoxide production induced by G-CSF treatment on the T lymphocyte functions remain to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that monocyte activation takes place during the tethering and initial interaction with platelets, leading to a high-affinity state of integrins for their ligands. In support of this concept is the finding that binding of P-selectin or activated platelets to monocytes induces intracellular signaling and activation [39][40][41].…”
Section: Ligands For Integrinsmentioning
confidence: 93%